2003
DOI: 10.5897/ajb2003.000-1066
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid profile of Escherichia coli 0157:H7 from apparently healthy animals

Abstract: One hundred samples from healthy animals were screened for the presence of enterohaemorrhagic Escherichia coli 0157: H7 and 17 were positive for EHEC 0157:H7 after confirmation using serology kits. Antibiotic susceptibility patterns showed the isolates to be highly susceptible to the various antibiotics screened with a few showing multiple antibiotic resistance. The plasmid profiles revealed that 8/17 (47%) of the animal isolates harboured detectable plasmids ranging in size from 0.564 kb to >23 kb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 7 publications
2
24
2
Order By: Relevance
“…Umolu et al 27 reported that E. coli Isolates with high multi-drug resistance profiles were found to possess multiple plasmids with large sizes in the range of 6.557 -23.130kb. This is also similar to what was observed by Smith et al 57 who reported that 47 of the E. coli isolated from animals in Lagos harboure detectable plasmids which ranged in sizes from 0.564kb to >23kb. Danbara et al 23 also reported plasmids of sizes between 3.9kb and 50kb in E. coli strains isolated from Traveller's diarrhoea.…”
supporting
confidence: 79%
“…Umolu et al 27 reported that E. coli Isolates with high multi-drug resistance profiles were found to possess multiple plasmids with large sizes in the range of 6.557 -23.130kb. This is also similar to what was observed by Smith et al 57 who reported that 47 of the E. coli isolated from animals in Lagos harboure detectable plasmids which ranged in sizes from 0.564kb to >23kb. Danbara et al 23 also reported plasmids of sizes between 3.9kb and 50kb in E. coli strains isolated from Traveller's diarrhoea.…”
supporting
confidence: 79%
“…The observed resistance in these strains may drive from antimicrobial selection pressure as a result of indiscriminate use of antimicrobials in livestock production in Nigeria (Smith et al 2003; or as a result of intrinsic resistance in these environmental strains. According to Martinez et al (2009), antibiotics have the function of inhibiting competitors in natural environments, hence the proposition that antibiotic resistance genes evolved to protect bacteria in natural ecosystems from the toxicity of such naturally occurring antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, absence of 60-MDa plasmid in other strains in this study does not confirm whether those are non-enterohaemorrhagic E. coli. Based on our observations, the isolates containing plasmids of large molecular weights are potential members of EHEC and they may be virulenceassociated as well as toxigenic 11 . Association of plasmid DNA with antimicrobial resistance of E. coli as well as EHEC was described earlier 16 .…”
Section: Multidrug-resistant (Mdr) Patternmentioning
confidence: 86%
“…Association of plasmid DNA with antimicrobial resistance of E. coli as well as EHEC was described earlier 16 . Particularly, implication of large plasmid with multiple-drug resistance was broadly highlighted 11 . In the present study, we have successfully isolated nine large-plasmid containing strains, which showed remarkable resistance to a panel of carefully chosen antibiotics.…”
Section: Multidrug-resistant (Mdr) Patternmentioning
confidence: 99%
See 1 more Smart Citation